Nanoparticle reinforced polytetrafluoroethylene pipe and preparation method thereof

By introducing modified nanoboronitride into polytetrafluoroethylene and processing through specific processes to form nanoparticle-enhanced polytetrafluoroethylene pipes, the problem of poor wear resistance of polytetrafluoroethylene pipes is solved, and the mechanical properties and wear resistance of the material are significantly improved.

CN119684733AActive Publication Date: 2025-03-25ZHEJIANG YOUFUMI VALVE CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510220095.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

Poor wear resistance of PTFE pipes limit their use in applications requiring high strength and wear resistance.

Method used

Nanoparticle-reinforced polytetrafluoroethylene pipe is formed by introducing modified nanoboronitride into polytetrafluoroethylene and by melt stirring and extrusion molding. The modified nanoboronitride improves the compatibility and mechanical properties of the material through the introduction of fluorine chains and the use of crosslinking agents.

Benefits of technology

The tensile strength, elongation of break and wear resistance of the material are significantly improved, and the wear volume is reduced by 70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of pipes, in particular to a nano-particle reinforced polytetrafluoroethylene pipe and a preparation method thereof. The nano-particle reinforced polytetrafluoroethylene pipe is obtained by carrying out extrusion molding and high-temperature sintering on nano-particle reinforced polytetrafluoroethylene master batches; the nano-particle reinforced polytetrafluoroethylene master batch is obtained by melting, stirring, extruding and granulating modified nano boron nitride and polytetrafluoroethylene powder; wherein the modified nano boron nitride is obtained by wrapping a cross-linked network constructed by perfluorohexyl ethyl methacrylate, ethyl methacrylate and trimethylolpropane triacrylate. The nano-particle reinforced polytetrafluoroethylene pipe prepared by the invention has excellent mechanical properties and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pipes, and in particular to a nano-particle-reinforced polytetrafluoroethylene pipe and a preparation method thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE) tubing is widely used in chemical, electronic, and mechanical fields due to its excellent chemical inertness, high temperature resistance, and low friction coefficient. However, the inherent defects of PTFE, such as low mechanical strength and wear resistance, limit its use in applications that require high strength and wear resistance. In order to overcome these shortcomings, researchers have tried to improve the performance of PTFE through various modification methods. Traditionally, adding fillers (such as glass fiber, carbon fiber, etc.) is a way to enhance the performance of PTFE, but this usually leads to a decrease in other properties of the material.

[0003] In recent years, the introduction of nanomaterials has provided new possibilities for the modification of PTFE. Nano boron nitride (BN) has become an ideal choice for reinforcing PTFE due to its excellent thermal stability and mechanical properties. However, although directly adding nano boron nitride to PTFE can improve the performance of the material to a certain extent, it is difficult to achieve the ideal reinforcement effect due to poor interfacial compatibility. Therefore, how to improve the compatibility of nano boron nitride with the PTFE matrix and thus significantly improve the comprehensive performance of PTFE has become the focus of current research. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a nanoparticle-reinforced polytetrafluoroethylene pipe and a preparation method thereof to solve the problem of poor wear resistance of the polytetrafluoroethylene pipe.

[0005] Based on the above purpose, the present invention provides a nanoparticle reinforced polytetrafluoroethylene pipe, which is obtained by extruding and high-temperature sintering nanoparticle reinforced polytetrafluoroethylene masterbatch.

[0006] Furthermore, the nano-particle-reinforced polytetrafluoroethylene masterbatch is obtained by melting and stirring modified nano-boron nitride and polytetrafluoroethylene powder, and then extruding and granulating.

[0007] Furthermore, the weight ratio of the modified nano boron nitride to polytetrafluoroethylene powder is 30-70:1000.

[0008] Furthermore, the preparation method of the modified nano boron nitride is as follows: (1) Under a nitrogen atmosphere, hydroxylated nano-boron nitride and triethylamine are added to tetrahydrofuran, ultrasonicated for 10-30 minutes, stirred for 20-40 minutes, and then 2-bromoisobutyryl bromide is added. The temperature is lowered to -5-0°C, stirred for 2-4 hours, then heated to room temperature, stirred for 36-60 hours, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (2) Under a nitrogen atmosphere, nano boron nitride containing initiation sites on the surface, copper chloride, perfluorohexylethyl methacrylate, ethyl methacrylate, trimethylolpropane triacrylate and tetrahydrofuran are mixed and stirred for 20-40 minutes, and then 1,1,4,7,10,10-hexamethyltriethylenetetramine is added, the temperature is raised to 65-75°C, and the mixture is stirred for 40-55 hours. Perfluorohexylethyl methacrylate is then added dropwise, and after the addition is complete, the mixture is stirred for 10-14 hours, centrifuged, washed, and dried to obtain modified nano boron nitride.

[0009] Preferably, in step (1), the weight ratio of hydroxylated nano-boron nitride, triethylamine, tetrahydrofuran and 2-bromoisobutyryl bromide is 30-70:7-20:300-700:6-18.

[0010] Preferably, in step (2), the weight ratio of nano boron nitride having initiation sites on the surface, copper chloride, perfluorohexylethyl methacrylate, ethyl methacrylate, trimethylolpropane triacrylate, tetrahydrofuran and 1,1,4,7,10,10-hexamethyltriethylenetetramine is 30-70:10-20:40-100:150-250:5-20:200-300:35-70.

[0011] Preferably, in the step (2), the weight ratio of the perfluorohexylethyl methacrylate added for the first time to the perfluorohexylethyl methacrylate added for the second time is 3-7:1-3.

[0012] Preferably, the average particle size of the polytetrafluoroethylene powder is 100-300 μm.

[0013] Preferably, the temperature of the melt stirring is 440-460° C. and the time is 1.5-2.5 h.

[0014] Preferably, the preparation method of the hydroxylated nano-boron nitride is as follows: disperse the nano-boron nitride in deionized water, then add sodium hydroxide, heat to 55-65° C., stir for 10-15 hours, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride.

[0015] Preferably, the average particle size of the nano boron nitride is 20-100 nm.

[0016] Preferably, the weight ratio of the nano-boron nitride, deionized water and sodium hydroxide is 30-70:300-700:50-200.

[0017] Furthermore, the present invention also provides a method for preparing a nanoparticle-reinforced polytetrafluoroethylene pipe, comprising the following steps: placing nanoparticle-reinforced polytetrafluoroethylene masterbatch into a mold for preforming to form a cylindrical blank, then placing the cylindrical blank into an extruder to extrude it to form a tubular material, and finally sintering the tubular material and cooling it to obtain a nanoparticle-reinforced polytetrafluoroethylene pipe.

[0018] Preferably, the sintering temperature is 350-370° C. and the sintering time is 2.5-3.5 h.

[0019] Beneficial effects of the present invention: The present invention significantly improves the mechanical properties and wear resistance of the material by preparing a nanoparticle-reinforced polytetrafluoroethylene pipe. Compared with a polytetrafluoroethylene pipe directly added with nano boron nitride, the pipe of the present invention exhibits higher performance in terms of tensile strength and elongation at break, especially in terms of wear resistance, with the wear volume reduced by 70%.

[0020] The introduction of fluorine chains outside nano-boron nitride significantly improves the tensile strength and elongation at break of the material. The presence of fluorine chains promotes the penetration of polytetrafluoroethylene molecular chains into the polymer network on the surface of nano-boron nitride during the melting process, forming a mechanical interlocking structure. This structure not only enhances the compatibility of nano-boron nitride and polytetrafluoroethylene, but also greatly improves the wear resistance of the material. The use of trimethylolpropane triacrylate as a cross-linking agent further improves the mechanical properties and wear resistance of the pipe. The cross-linking agent helps to build a network structure in nano-boron nitride, providing more space for the interlacing of polytetrafluoroethylene molecular chains, thereby enhancing the overall strength and wear resistance of the material. In addition, the secondary addition of perfluorohexylethyl methacrylate forms a linear fluorine chain on the surface of nano-boron nitride, which not only improves the compatibility with polytetrafluoroethylene, but also enhances the interaction between nano-boron nitride and polytetrafluoroethylene matrix by entanglement with polytetrafluoroethylene molecular chains. This enhanced interaction further improves the mechanical properties and wear resistance of the material. DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0022] The average particle size of the polytetrafluoroethylene powder in the specific embodiment of the present invention is 200 μm, and the average particle size of the nano boron nitride is 50 nm. Embodiment 1:

[0023] (1) Disperse 30 g of nano-boron nitride in 300 g of deionized water, then add 50 g of sodium hydroxide, heat to 55 ° C, stir for 10 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 30 g of hydroxylated nano-boron nitride and 7 g of triethylamine were added to 300 g of tetrahydrofuran, ultrasonicated for 10 min, stirred for 20 min, and then 6 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to -5 °C, stirred for 2 h, then raised to room temperature, stirred for 36 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under a nitrogen atmosphere, 30 g of nano boron nitride with initiation sites on the surface, 10 g of copper chloride, 30 g of perfluorohexylethyl methacrylate, 150 g of ethyl methacrylate, 5 g of trimethylolpropane triacrylate and 200 g of tetrahydrofuran were mixed and stirred for 20 min, then 35 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 65°C, stirred for 40 h, and then 10 g of perfluorohexylethyl methacrylate was added dropwise. After the addition was complete, the mixture was stirred for 10 h, centrifuged, washed and dried to obtain modified nano boron nitride; (4) 30 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 440 °C, stirred for 1.5 h, and then extruded and granulated to obtain nanoparticle-reinforced polytetrafluoroethylene masterbatch. The nanoparticle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 350 °C for 2.5 h and cooled to obtain a nanoparticle-reinforced polytetrafluoroethylene tube. Embodiment 2:

[0024] (1) Disperse 50 g of nano-boron nitride in 500 g of deionized water, then add 100 g of sodium hydroxide, heat to 60 ° C, stir for 12 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 50 g of hydroxylated nano-boron nitride and 12.5 g of triethylamine were added to 500 g of tetrahydrofuran, ultrasonicated for 20 min, stirred for 30 min, and then 12 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to 0 ° C, stirred for 3 h, then raised to room temperature, stirred for 48 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under a nitrogen atmosphere, 50 g of nano boron nitride with initiation sites on the surface, 15 g of copper chloride, 50 g of perfluorohexylethyl methacrylate, 200 g of ethyl methacrylate, 10 g of trimethylolpropane triacrylate and 250 g of tetrahydrofuran were mixed and stirred for 30 min, then 50 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 70°C, stirred for 48 h, and then 20 g of perfluorohexylethyl methacrylate was added dropwise. After the addition was complete, the mixture was stirred for 12 h, centrifuged, washed and dried to obtain modified nano boron nitride; (4) 50 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 450 ° C, stirred for 2 h, and then extruded and granulated to obtain nanoparticle-reinforced polytetrafluoroethylene masterbatch. The nanoparticle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 360 ° C for 3 h and cooled to obtain a nanoparticle-reinforced polytetrafluoroethylene tube. Embodiment 3:

[0025] (1) Disperse 70 g of nano-boron nitride in 700 g of deionized water, then add 200 g of sodium hydroxide, heat to 65 ° C, stir for 15 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 70 g of hydroxylated nano-boron nitride and 20 g of triethylamine were added to 700 g of tetrahydrofuran, ultrasonicated for 30 min, stirred for 40 min, and then 18 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to 0 ° C, stirred for 4 h, then raised to room temperature, stirred for 60 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under nitrogen atmosphere, 70 g of nano boron nitride with initiation sites on the surface, 20 g of copper chloride, 70 g of perfluorohexylethyl methacrylate, 250 g of ethyl methacrylate, 20 g of trimethylolpropane triacrylate and 300 g of tetrahydrofuran were mixed and stirred for 40 min, then 70 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 75°C, stirred for 55 h, and then 30 g of perfluorohexylethyl methacrylate was added dropwise. After the addition was complete, the mixture was stirred for 14 h, centrifuged, washed and dried to obtain modified nano boron nitride; (4) 70 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 460 ° C, stirred for 2 h, and then extruded and granulated to obtain nanoparticle-reinforced polytetrafluoroethylene masterbatch. The nanoparticle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 370 ° C for 3.5 h and cooled to obtain a nanoparticle-reinforced polytetrafluoroethylene tube.

[0026] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the perfluorohexylethyl methacrylate in step (3) is replaced by ethyl methacrylate; The specific steps are as follows: (1) Disperse 50 g of nano-boron nitride in 500 g of deionized water, then add 100 g of sodium hydroxide, heat to 60 ° C, stir for 12 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 50 g of hydroxylated nano-boron nitride and 12.5 g of triethylamine were added to 500 g of tetrahydrofuran, ultrasonicated for 20 min, stirred for 30 min, and then 12 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to 0 ° C, stirred for 3 h, then raised to room temperature, stirred for 48 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under a nitrogen atmosphere, 50 g of nano-boron nitride with initiation sites on the surface, 15 g of copper chloride, 250 g of ethyl methacrylate, 10 g of trimethylolpropane triacrylate and 250 g of tetrahydrofuran were mixed and stirred for 30 min, then 50 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 70°C, stirred for 48 h, and then 20 g of ethyl methacrylate was added dropwise. After the addition was complete, the mixture was stirred for 12 h, centrifuged, washed and dried to obtain modified nano-boron nitride; (4) 50 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 450°C, stirred for 2 h, and then extruded and granulated to obtain nano-particle-reinforced polytetrafluoroethylene masterbatch. The nano-particle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 360°C for 3 h and cooled to obtain a polytetrafluoroethylene tube.

[0027] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the trimethylolpropane triacrylate in step (3) is replaced by ethyl methacrylate; The specific preparation steps are as follows: (1) Disperse 50 g of nano-boron nitride in 500 g of deionized water, then add 100 g of sodium hydroxide, heat to 60 ° C, stir for 12 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 50 g of hydroxylated nano-boron nitride and 12.5 g of triethylamine were added to 500 g of tetrahydrofuran, ultrasonicated for 20 min, stirred for 30 min, and then 12 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to 0 ° C, stirred for 3 h, then raised to room temperature, stirred for 48 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under a nitrogen atmosphere, 50 g of nano boron nitride with initiation sites on the surface, 15 g of copper chloride, 50 g of perfluorohexylethyl methacrylate, 210 g of ethyl methacrylate and 250 g of tetrahydrofuran were mixed and stirred for 30 min, then 50 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 70°C, stirred for 48 h, and then 20 g of perfluorohexylethyl methacrylate was added dropwise. After the addition was complete, the mixture was stirred for 12 h, centrifuged, washed and dried to obtain modified nano boron nitride; (4) 50 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 450°C, stirred for 2 h, and then extruded and granulated to obtain nano-particle-reinforced polytetrafluoroethylene masterbatch. The nano-particle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 360°C for 3 h and cooled to obtain a polytetrafluoroethylene tube.

[0028] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that: in step (3), no secondary addition of perfluorohexylethyl methacrylate is performed; The specific preparation steps are as follows: (1) Disperse 50 g of nano-boron nitride in 500 g of deionized water, then add 100 g of sodium hydroxide, heat to 60 ° C, stir for 12 h, centrifuge, wash, and dry to obtain hydroxylated nano-boron nitride; (2) Under nitrogen atmosphere, 50 g of hydroxylated nano-boron nitride and 12.5 g of triethylamine were added to 500 g of tetrahydrofuran, ultrasonicated for 20 min, stirred for 30 min, and then 12 g of 2-bromoisobutyryl bromide was added. The temperature was lowered to 0 ° C, stirred for 3 h, then raised to room temperature, stirred for 48 h, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (3) Under a nitrogen atmosphere, 50 g of nano boron nitride with initiation sites on the surface, 15 g of copper chloride, 50 g of perfluorohexylethyl methacrylate, 200 g of ethyl methacrylate, 10 g of trimethylolpropane triacrylate and 250 g of tetrahydrofuran were mixed and stirred for 30 min, and then 50 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine was added, the temperature was raised to 70°C, stirred for 48 h, centrifuged, washed and dried to obtain modified nano boron nitride; (4) 50 g of modified nano-boron nitride and 1000 g of polytetrafluoroethylene powder were melted at 450°C, stirred for 2 h, and then extruded and granulated to obtain nano-particle-reinforced polytetrafluoroethylene masterbatch. The nano-particle-reinforced polytetrafluoroethylene masterbatch was then loaded into a mold for preforming to form a cylindrical billet. The cylindrical billet was then placed in an extruder and extruded to form a tubular material. Finally, the tubular material was sintered at 360°C for 3 h and cooled to obtain a polytetrafluoroethylene tube.

[0029] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the modified nano-boron nitride in step (4) is replaced by nano-boron nitride; The specific preparation steps are as follows: 50g of nano boron nitride and 1000g of polytetrafluoroethylene powder are melted at 450°C, stirred for 2h, and then extruded and granulated to obtain nano particle reinforced polytetrafluoroethylene masterbatch, and then the nano particle reinforced polytetrafluoroethylene masterbatch is loaded into a mold for preforming to form a cylindrical billet, and then the cylindrical billet is put into an extruder and extruded to form a tubular material, and finally the tubular material is sintered at 360°C for 3h and cooled to obtain a nano particle reinforced polytetrafluoroethylene pipe.

[0030] Performance Test: Tensile properties test: carried out on a universal testing machine according to GB / T 1040-1992. The results are shown in Table 1.

[0031] Wear resistance: On a multifunctional friction and wear testing machine, the tribological properties of the material surface were tested by a reciprocating sliding friction and wear test in a ball-plane contact mode. The friction pair was a GCr15 bearing steel ball with a diameter of 10 mm, the normal load was 7 N, the reciprocating displacement was 10 mm, the frequency was 2 Hz, and the reciprocating sliding time was 3600 s. Ten samples were tested for each embodiment and comparative example, and the wear volume of the sample surface was measured using a laser confocal microscope. The average value was taken. The results are shown in Table 1.

[0032] Table 1 Performance test results

[0033] Data Analysis: It can be seen from the data of Examples 1-3 and Comparative Example 4 in Table 1 that, compared with directly adding nano-boron nitride, the nanoparticle-reinforced polytetrafluoroethylene pipe prepared by the present invention has higher tensile strength and elongation at break, and most importantly, the wear resistance is greatly improved. Compared with the polytetrafluoroethylene pipe directly adding nano-boron nitride, the wear volume is reduced by 70%.

[0034] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the introduction of fluorine chains outside nano-boron nitride helps to further improve the tensile strength and elongation at break, and has an outstanding contribution to the improvement of wear resistance. This is mainly because the introduction of fluorine chains helps the molecular chains of polytetrafluoroethylene to penetrate into the polymer network on the surface of nano-boron nitride during the melting process, thereby forming a mechanical interlocking structure and improving the compatibility of nano-boron nitride and polytetrafluoroethylene.

[0035] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that trimethylolpropane triacrylate as a cross-linking agent helps to improve the mechanical properties and wear resistance of the pipe. This is mainly because trimethylolpropane triacrylate helps to build a network structure in nano-boron nitride, providing space for the interlacing of polytetrafluoroethylene molecular chains.

[0036] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that the secondary addition of perfluorohexylethyl methacrylate helps to improve the mechanical properties and wear resistance of the pipe. This is mainly because the secondary addition of perfluorohexylethyl methacrylate can form linear fluorine chains in the outer layer of the surface network structure of nano-boron nitride, which on the one hand improves the compatibility with polytetrafluoroethylene, and on the other hand can form entanglement with the molecular chain of polytetrafluoroethylene, thereby improving the interaction between nano-boron nitride and polytetrafluoroethylene matrix.

[0037] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A nanoparticle-reinforced polytetrafluoroethylene pipe, characterized in that: It is obtained by extruding nanoparticle-reinforced polytetrafluoroethylene masterbatch and sintering at high temperature; The nano-particle-reinforced polytetrafluoroethylene masterbatch is obtained by melting and stirring modified nano-boron nitride and polytetrafluoroethylene powder, and then extruding and granulating. The weight ratio of the modified nano boron nitride to polytetrafluoroethylene powder is 30-70:1000; The preparation method of the modified nano boron nitride is as follows: (1) Under a nitrogen atmosphere, hydroxylated nano-boron nitride and triethylamine are added to tetrahydrofuran, ultrasonicated for 10-30 minutes, stirred for 20-40 minutes, and then 2-bromoisobutyryl bromide is added. The temperature is lowered to -5-0°C, stirred for 2-4 hours, then heated to room temperature, stirred for 36-60 hours, centrifuged, washed, and dried to obtain nano-boron nitride with initiation sites on the surface; (2) In a nitrogen atmosphere, nano boron nitride with initiation sites on the surface, copper chloride, perfluorohexylethyl methacrylate, ethyl methacrylate, trimethylolpropane triacrylate and tetrahydrofuran are mixed and stirred for 20-40 minutes, and then 1,1,4,7,10,10-hexamethyltriethylenetetramine is added, the temperature is raised to 65-75°C, and the mixture is stirred for 40-55 hours. Then, perfluorohexylethyl methacrylate is added dropwise, and after the addition is completed, the mixture is stirred for 10-14 hours, centrifuged, washed, and dried to obtain modified nano boron nitride; In the step (1), the weight ratio of hydroxylated nano-boron nitride, triethylamine, tetrahydrofuran and 2-bromoisobutyryl bromide is 30-70:7-20:300-700:6-18; In the step (2), the weight ratio of the nano boron nitride having the initiation site on the surface, copper chloride, perfluorohexylethyl methacrylate, ethyl methacrylate, trimethylolpropane triacrylate, tetrahydrofuran and 1,1,4,7,10,10-hexamethyltriethylenetetramine is 30-70:10-20:40-100:150-250:5-20:200-300:35-70; In the step (2), the weight ratio of the perfluorohexylethyl methacrylate added for the first time to the perfluorohexylethyl methacrylate added for the second time is 3-7:1-3.

2. The nanoparticle-reinforced polytetrafluoroethylene tube according to claim 1, characterized in that: The average particle size of the polytetrafluoroethylene powder is 100-300 μm.

3. The nanoparticle-reinforced polytetrafluoroethylene tube according to claim 1, characterized in that: The temperature of the melt stirring is 440-460° C., and the time is 1.5-2.5 h.

4. The nanoparticle-reinforced polytetrafluoroethylene tube according to claim 1, characterized in that: The preparation method of the hydroxylated nano boron nitride is as follows: disperse the nano boron nitride in deionized water, then add sodium hydroxide, heat to 55-65° C., stir for 10-15 hours, centrifuge, wash, and dry to obtain the hydroxylated nano boron nitride.

5. The nanoparticle-reinforced polytetrafluoroethylene tube according to claim 4, characterized in that: The average particle size of the nano boron nitride is 20-100 nm.

6. The nanoparticle-reinforced polytetrafluoroethylene tube according to claim 4, characterized in that: The weight ratio of the nano boron nitride, deionized water and sodium hydroxide is 30-70:300-700:50-200.

7. A method for preparing a nanoparticle-reinforced polytetrafluoroethylene tube according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: placing nano-particle-reinforced polytetrafluoroethylene master batch into a mold for preforming to form a cylindrical blank, placing the cylindrical blank into an extruder for extrusion to form a tubular material, and finally sintering and cooling the tubular material to obtain a nano-particle-reinforced polytetrafluoroethylene tubular material.

8. The method for preparing the nanoparticle-reinforced polytetrafluoroethylene pipe according to claim 7, characterized in that: The sintering temperature is 350-370° C. and the sintering time is 2.5-3.5 hours.

Citation Information

Patent Citations

  • Surface modification method of inorganic nanoparticles as well as polytetrafluoroethylene / inorganic nanoparticle composite material

    CN104479266A

  • Boron nitride-packed carbon nano-polytetrafluoroethylene valve sealing ring

    CN106084579A

  • Preparation method of compound dielectric material and compound dielectric material

    CN109593218A

  • Nano boron nitride in-situ grafted polystyrene with high thermal conductivity and preparation method thereof

    CN111471148A

  • Nano boron nitride grafted acrylic resin insulating material and preparation method thereof

    CN111848887A